1999
DOI: 10.1024/0301-1526.28.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and thrombotic vascular disease

Abstract: Homocysteine is a sulfur-containing amino acid intermediate involved in two metabolic pathways, in the remethylation to methionine and in the transsulfuration to cysteine. Severe hyperhomocysteinemia (> 100 mumol/l) is found in congenital homocystinuria. Moderate (15-30 mumol/l) or intermediate (> 30-100 mumol/l) hyperhomocysteinemia is caused by defects in genes encoding for enzymes of homocysteine metabolism or by inadequate intake of those vitamins that are involved in homocysteine metabolism (folic acid, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In adults, it is reported that isolated hyperhomocysteinemia may damage blood vessels, causing pulmonary arterial hypertension (PAH) and/or pulmonary thromboembolism [1, 2]. Both microangiopathy and thromboembolism can be the underlying mechanisms for pulmonary hypertension in CblC deficiency [38], but an association between MMA and/or homocysteinemia and diffuse lung disease (DLD) has not been broadly reported.…”
Section: Letter To the Editormentioning
confidence: 99%
“…In adults, it is reported that isolated hyperhomocysteinemia may damage blood vessels, causing pulmonary arterial hypertension (PAH) and/or pulmonary thromboembolism [1, 2]. Both microangiopathy and thromboembolism can be the underlying mechanisms for pulmonary hypertension in CblC deficiency [38], but an association between MMA and/or homocysteinemia and diffuse lung disease (DLD) has not been broadly reported.…”
Section: Letter To the Editormentioning
confidence: 99%